Hepatomas - Bogliaccini, Gustavo; Pomi, Jorge; Bagnulo, Homero; Praderi, Raúl (Cirugía del Uruguay, 1981)
33 cases of primitive liver tumors from the Clínicas Hospital, Macier Hospital and the · personal record of one of us ( R. P.).